2018
DOI: 10.3389/fmed.2018.00160
|View full text |Cite
|
Sign up to set email alerts
|

Physiology of Hyperuricemia and Urate-Lowering Treatments

Abstract: Gout is the most common form of inflammatory arthritis and is a multifactorial disease typically characterized by hyperuricemia and monosodium urate crystal deposition predominantly in, but not limited to, the joints and the urinary tract. The prevalence of gout and hyperuricemia has increased in developed countries over the past two decades and research into the area has become progressively more active. We review the current field of knowledge with emphasis on active areas of hyperuricemia research including… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
155
0
16

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 226 publications
(196 citation statements)
references
References 277 publications
(294 reference statements)
1
155
0
16
Order By: Relevance
“…It has been reported that urate caused inflammatory, proliferative, and irreversible changes in glomeruli and the tubulointerstitium via various cascades, such as renal vasoconstriction, renin-angiotensin system activation, and endothelial dysfunction [30,31]. In addition, it was shown that elevated uric acid level inhibited insulin signaling and induced insulin resistance in vivo and in vitro [32], which could act together with glucose transporter in development of CKD [31]. On the other hand, it has been suggested that low to moderate alcohol consumption increased insulin sensitivity [33][34][35][36][37].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been reported that urate caused inflammatory, proliferative, and irreversible changes in glomeruli and the tubulointerstitium via various cascades, such as renal vasoconstriction, renin-angiotensin system activation, and endothelial dysfunction [30,31]. In addition, it was shown that elevated uric acid level inhibited insulin signaling and induced insulin resistance in vivo and in vitro [32], which could act together with glucose transporter in development of CKD [31]. On the other hand, it has been suggested that low to moderate alcohol consumption increased insulin sensitivity [33][34][35][36][37].…”
Section: Discussionmentioning
confidence: 99%
“…First, we did not obtain information about the types of alcohol beverages. Although it is known that beer drinking increases serum uric acid, regardless of their purine content [31], wine drinking has the possibility of not increasing serum uric acid [38]. Second, we used alcohol drinking habits and covariates at baseline as the representative of alcohol consumption.…”
Section: Discussionmentioning
confidence: 99%
“…HU is mainly associated with the following: (1) alcohol consumption; (2) a fructose rich diet; (3) excess consumption of seafood or meat; (4) diuretics; (5) some medications; and (6) angiotensin converting enzymes [8,9]. Gout is associated with precipitation of monosodium urate (MSU) crystals in joints and soft tissues [10,11]. Deposition of MSU crystals in the big toe, some joints and the ankle are associated with neutrophil infiltration, swelling and pain [12].…”
Section: Introductionmentioning
confidence: 99%
“…Deposition of MSU crystals in the big toe, some joints and the ankle are associated with neutrophil infiltration, swelling and pain [12]. The first line of gout treatment is allopurinol (ALP), a xanthine oxidase inhibitor stimulating the renal secretion and excretion of UA [11]. Other anti-inflammatory non-steroidal drugs known to inhibit cyclooxygenase activity (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Примером такой приобретенной инфламмасомопатии является подагра. Сама гиперурикемия как предпосылка подагры может быть генетически обусловленной [6], однако аутовоспалительная подагрическая атака развивается как генетически нормальная реакция на гиперурикемию, не связанная с мутациями. В этом случае активация инфламмасомы связана с тем, что криопирин является внутриклеточным рецептором, который реагирует на различные патогены, в том числе кристаллические структуры (кристаллы мочевой кислоты, холестерина), оказавшиеся в кровотоке или интерстиции [5].…”
unclassified